Copper supplementation enhances pigmentation and induces dopamine production in ARPE19 - Hironori Uehara; Baila Shakaib; Sangeetha Ravi Kumar; Bonnie Archer; Balamurali Ambati (PLoS ONE, 2025)
Non-neuronal dopamine production has not been understood despite dopamine function in non-neuronal tissues. Tyrosinase is a non-neuronal enzyme which converts tyrosine to L-DOPA (l-3,4-dihydroxyphenylalanine) and L-DOPA to l-dopaquinone for further melanin production. Since L-DOPA is a dopamine precursor in neurons, we hypothesized that tyrosinase-derived L-DOPA could alternatively be converted to dopamine. Therefore, this study investigated whether copper supplementation enhanced pigmentation and induced dopamine production via tyrosinase activation in APRE19 cells. Copper is known as a tyrosinase cofactor. In two separate experiments, we cultured ARPE19 in 1% FBS/DMEM with/without 10 μM copper sulfate for approximately 100 days. After 40–50 days, slight pigmentation with copper treatment was confirmed in the cell pellets, while no pigmentation was observed in the non-copper control. After 90–100 days, the pigmentation in the copper treatment group was obvious, while minimal pigmentation was observed in the non-copper control. Dopamine was not detected at 40–50 days in either group, while it was detected after 90–100 days of culture only in the copper-treated group. Tyrosinase mRNA expression was confirmed in both groups at a similar level, while tyrosinase protein expression was significantly higher in the copper treatment group than in the non-copper control. Thus, we determined that copper supplementation efficiently enhances pigmentation and induces dopamine production in long-term culture ARPE19, likely due to increased tyrosinase protein expression and activity. This is the first report showing the significance of copper in non-neuronal dopamine production of RPE cells, which suggests that tyrosinase may be responsible for non-neuronal dopamine production.